Synthesis of novel pyrimidine and fused pyrimidine derivatives - Mahmoud, Mahmoud Refaee; El-Ziaty, Ahmed Kamel; Ismail, Mahmoud Fawzy; Shiba, Sayed Ahmed (European Journal of Chemistry, 2011)
4-Amino-2-(benzylthio)-6-(4-methoxyphenyl)pyrimidine-5-carbonitrile (1) was prepared by treatment of s-benzylthiuronium chloride with 2-(4-methoxybenzylidene)malononitrile in ethanolic sodium hydroxide with hydrazine hydrate to afford the hydrazino derivative 2, which was allowed to react with different electrophilic reagents to give the pyrimidine derivatives 3-12. The proclivity of (E)-2-cyano-3-(4-nitrophenyl)acrylamide (13) towards carbon and nitrogen nucleophiles was also investigated. IR, 1H NMR and mass spectra for all the synthesized compounds were discussed. All derived compounds were investigated for anti avian influenza (H5N1) virus activity and compared with zanamivir as control drug. All the synthesized compounds didn’t possess any antiviral activity.